'Working together is like a partnership of entangled knowledge': exploring the sensitivities of doing participatory data analysis with people with learning disabilities. Issue 5 (3rd September 2021) - Tilley, Elizabeth; Strnadová, Iva; Ledger, Sue; Walmsley, Jan; Loblinzk, Julie; Christian, Paul Anthoney; Arnold, Zara Jane
ABSTRACT: While there have been significant developments in the field of inclusive research with people with learning disabilities, there is limited knowledge about the ways inclusive research teams have conducted participatory data analysis. The authors argue this is inherently tied to the sensitivities involved in the inclusive research process. In this article, we present the experiences of two inclusive research teams (from the UK and Australia) who developed ways of working together to collaborate on data analysis. Both studies touched upon sensitive topics and crossed disciplinary boundaries. One was an evaluation of a series of history workshops with young people with learning disabilities; the other was an exploration of effective models of peer support for parents with learning disabilities. The authors explore different approaches to data analysis in inclusive research teams, and reflect on the politics of 'sensitive' research in this field, especially in relation to expectations of funders, ethics committees, and stakeholders.